2004
DOI: 10.1161/01.cir.0000131515.03336.f8
|View full text |Cite
|
Sign up to set email alerts
|

Role of Endothelial Dysfunction in Atherosclerosis

Abstract: Abstract-As the major regulator of vascular homeostasis, the endothelium exerts a number of vasoprotective effects, such as vasodilation, suppression of smooth muscle cell growth, and inhibition of inflammatory responses. Many of these effects are largely mediated by nitric oxide, the most potent endogenous vasodilator. Nitric oxide opposes the effects of endothelium-derived vasoconstrictors and inhibits oxidation of low-density lipoprotein. A defect in the production or activity of nitric oxide leads to endot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
1,572
2
91

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,894 publications
(1,687 citation statements)
references
References 76 publications
(62 reference statements)
22
1,572
2
91
Order By: Relevance
“…Similar findings have been previously reported in children with type 1 diabetes mellitus; endothelial dysfunction was reported in the absence of structural atherosclerotic changes (37). Previous studies in various populations have shown that endothelial dysfunction is detected long before the angiographic appearance of atherosclerosis on the vessel wall (22) and has been reported to predict the progression of carotid IMT (38). It could be speculated that JIA may be primarily associated with endothelial dysfunction, apparent even at ages 7-10 years, independently of the presence of systemic or nonsystemic disease.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar findings have been previously reported in children with type 1 diabetes mellitus; endothelial dysfunction was reported in the absence of structural atherosclerotic changes (37). Previous studies in various populations have shown that endothelial dysfunction is detected long before the angiographic appearance of atherosclerosis on the vessel wall (22) and has been reported to predict the progression of carotid IMT (38). It could be speculated that JIA may be primarily associated with endothelial dysfunction, apparent even at ages 7-10 years, independently of the presence of systemic or nonsystemic disease.…”
Section: Discussionsupporting
confidence: 89%
“…Endothelial dysfunction, detected early in the atherosclerotic process, is known to play an important role in the initiation and progression of atherosclerosis (22). Decreased brachial FMD has been associated with increased long-term incidence of cardiovascular events in healthy adults or CVD patients (6).…”
Section: Discussionmentioning
confidence: 99%
“…The protective effects of NO on the cardiovascular system are well documented29, 30, 31; NO functionally inhibits platelet aggregation, leukocyte adhesion, and smooth muscle cell proliferation and maintains vascular tone, thereby maintaining cardiovascular homeostasis and preventing cardiovascular diseases 32, 33, 34. However, at the initial stage of several cardiovascular diseases, oxidative stress uncouples eNOS‐derived NO, thereby increasing ONOO‐ production, which deregulates eNOS activity and leads to disease progression 35, 36, 37, 38. Statins can effectively lower cholesterol levels and reduce cardiovascular events in patients with various risk profiles 1, 2, 3, 4, 5.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic targeting of different inflammatory pathways might be effective in preventing and treating cardiovascular diseases 35, 36, 37. The endothelium, as the key regulator of vascular homeostasis, has vasoprotective properties, including anti‐inflammatory response and vasodilation 38. Endothelial dysfunction is regarded as the primary driver of atherosclerotic disease 39.…”
Section: Discussionmentioning
confidence: 99%